Pilot investigation of the association between serum stress neuropeptide levels and lymphocyte expression of fas and fas ligand in critical illness - Papathanassoglou, Elizabeth; Mpouzika, Meropi; Giannakopoulou, Margarita; Bozas, Evangelos; Middleton, Nicos; Boti, Sofia; Karabinis, Andreas (My University, 2015)
In critical illness, apoptotic loss of immunocytes is associated with immunosuppression. Aim:to explore expression of Fas/Fas ligand (FasL) on B and T cells from critically ill patients without sepsis compared to matched controls and associations with disease severity and neuropeptide Y (NPY), cortisol, adrenocorticotropic hormone (ACTH), and prolactin (PRL) levels. Methods: Repeated-measures correlational design with 36 critically ill patients (14-day follow-up) and 36 controls. Disease severity was assessed using the Multiple Organ Dysfunction Score (MODS) and Multi Organ Failure scale.Fas/FasL values were standardized for viable cell counts. An enzyme-linked immunosorbent assay (NPY) and electrochemiluminescence immunoassay (cortisol, ACTH, and PRL) were employed. Results: Fas and FasL expression on T-helper (p < .0001–.03)and T-cytotoxic cells (p < .0001–.002) and Fas expression on B cells (p < .0001–.03) were higher in patients. MODS severity was associated with FasL expression on cytotoxic T cells (r ¼ .752–.902, p ¼ .023–.037). There was an inverse association between Day 1 NPY levels and Fas expression on T-helper cells (r ¼ .447, p ¼ .019). On the day of maximum severity, we report for the first time an inverse association between NPY levels and FasL expression on helper (r ¼ .733, p ¼ .016) and cytotoxic (r ¼.862, p ¼ .003) T cells. Cortisol levels were positively associated with counts of FasL-positive helper (r ¼ .828) and cytotoxic(r ¼ .544, p < .05) T cells. Conclusion: Results suggest a potential role for stress neuropeptides in lymphocyte survival and activation in critical illness.
Keywords: Neuropeptides; Apoptosis; Stress; Critical illness; PBMC